Factors affecting gold production in Zimbabwe (1980–2018) - Sanderson, Abel; Thomas, Lusiyano; Tafirenyika, Mafugu (Elsevier, 2022)
The debate on the ‘resource curse’ or ‘the paradox of plenty’ has been raging for decades, albeit with no consensus. This is due to the diversity of findings from empirical literature supporting either side of the debate. The resource curse itself has been compartmentalised into several variants of the model, depending on the perceived causes and channels through which its effects are transmitted into the economy. Zimbabwe has been classified as a natural resource-abundant country by the World Bank. This paper broadly aims to evaluate the determinants of gold production in Zimbabwe during the period 1980 to 2018. Zimbabwe has an estimated 13 million tons of gold in situ. However, the country has not been able to fully exploit this resource – production has been intermittent and cyclical. Econometric modelling of the determinants of gold production shows that international gold price appears to be negatively related to gold production in Zimbabwe. This counter-intuitive result is explained by the greater impact of domestic economic conditions. Foreign currency retention, political stability, and gross capital formation are all positively related to gold production. It is recommended that Zimbabwe considers liberalizing the gold trading regime and institutes greater political stability and strengthen its institutions to stimulate gold production.